Physicochemical Parameters, Mineral Composition, and Nutraceutical Properties of Ready-to-Drink Flavored-Colored Commercial Teas - Daniel Flores-Martínez; Vania Urías-Orona; Luis Hernández-García; Werner Rubio-Carrasco; Korev Silva-Gutiérrez; Michelle Guevara-Zambrano; Julio Prieto-Cadena; Teresa Serna-Méndez; Dolores Muy-Rangel; Guillermo Niño-Medina (Journal of Chemistry)
The physicochemical parameters, mineral composition, and nutraceutical properties of ready-to-drink flavored-colored commercial teas were analyzed in the present study. The pH of samples was slightly acidic (3.72 to 4.11), titratable acidity was low (0.092 to 0.174%), and color parameters were wide variable (pink, yellow, brown, and red). Citrus-flavored tea obtained the highest content of manganese (0.281 mg·L−1), zinc (0.069 mg·L−1), magnesium (2.92 mg·L−1), potassium (62.65 mg·L−1), and sodium (271.74 mg·L−1), while lemon-, peach-, and blueberry-flavored teas obtained the highest levels of copper (0.035 mg·L−1), iron (0.246 mg·L−1), and calcium (18.21 mg·L−1), respectively. Citrus, lemon-, sangria-, and rose petal-flavored teas obtained the highest content in total phenols (211.56 mg·L−1), total flavonoids (65.46 mg·L−1), total catechins (640.79 mg·L−1), and total anthocyanins (640.79 mg·L−1), respectively. Lemon- and rose petal-flavored teas showed the highest and lowest antioxidant capacity levels in DPPH (1096.00 to 118.77 μmolTE·L−1), ABTS (1048.84 to 232.00 μmolTE·L−1), and FRAP (1269.20 to 147.70 μmolTE·L−1) assays. The levels of sodium reported in labels of all samples were lower than data obtained in our analysis. Also the levels observed for total phenols in blueberry-, citrus-, and rose petal-flavored teas were lower than our analysis, but total phenols of lemon-, peach-, and sangria-flavored teas were higher than the content reported in their labels. The results obtained in the present work give information to consumers for choosing flavored-colored ready-to-drink tea based on the physicochemical, nutritional, and nutraceutical properties.